2016
DOI: 10.1186/s13063-016-1738-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of community groups and mobile phone messages on the prevention and control of diabetes in rural Bangladesh: study protocol for a three-arm cluster randomised controlled trial

Abstract: BackgroundIncreasing rates of type 2 diabetes mellitus place a substantial burden on health care services, communities, families and individuals living with the disease or at risk of developing it. Estimates of the combined prevalence of intermediate hyperglycaemia and diabetes in Bangladesh vary, and can be as high as 30% of the adult population. Despite such high prevalence, awareness and control of diabetes and its risk factors are limited. Prevention and control of diabetes and its complications demand inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 37 publications
0
40
0
Order By: Relevance
“…Participants in the control arm requested for the intervention to be implemented in their own DSGs as they felt left out. This was already planned to meet the ethical obligation to ensure that control groups also benefit from the intervention [18]. This implementation in control arm DSGs was implemented subsequent to the trial.…”
Section: Inner Settingmentioning
confidence: 99%
“…Participants in the control arm requested for the intervention to be implemented in their own DSGs as they felt left out. This was already planned to meet the ethical obligation to ensure that control groups also benefit from the intervention [18]. This implementation in control arm DSGs was implemented subsequent to the trial.…”
Section: Inner Settingmentioning
confidence: 99%
“…23 Our research partnership between the University College London Institute for Global Health and the Diabetic Association of Bangladesh conducted formative research to inform the development of two interventions that have been evaluated through a three arm cluster randomized controlled trial testing their effectiveness on noncommunicable disease risk factors, including lack of physical activity, overweight and obesity, and intermediate hyperglycaemia and diabetes. 24 One intervention was a mobile health (mHealth) intervention informed by the capability, opportunity, motivation theory of behaviour change (COM-B), 25,26 and the other was a group-based community mobilization intervention using participatory learning and action (PLA) cycles to promote healthy behaviours and transform communities. 27,28 Both approaches (COM-B and PLA) acknowledge the socially constructed nature of behaviours, social constraints on behaviour and the need to address these to enable behaviour change.…”
Section: Gender and Behaviour Changementioning
confidence: 99%
“…The overall primary outcome of the trial was the reduction in the prevalence of intermediate hyperglycaemia and T2DM and a decrease in the two-year cumulative incidence of T2DM among individuals with intermediate hyperglycaemia [12]. Secondary and explanatory trial outcomes include a range of outcomes related to risk factors, awareness and control of diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…from the formative research as well as the secondary trial outcomes (reported in full elsewhere [12]). Having a clear understanding of the intended consequences of the intervention helped focus the messages of the intervention as well as identify the barriers and enablers to achieving them.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation